METODE LISTENING TEAM MELVIN L. SILBERMAN DALAM PEMBELAJARAN PENDIDIKAN ISLAM - Ahmad Ma'ruf; Cahyati Khasani (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
The use of methods that are too monotonous and less varied will affect student learning outcomes. Conversely, when a teacher uses a varied and fun method, it is able to develop students' knowledge optimally. According to some education experts, one method that can develop students' knowledge is the listening team method. This learning method is offered by Melvin L Silberman in his book active learning which contains 101 models of active learning strategies including the Listening Team learning method. In this study, the aim of this research is to answer the problem, namely: "What is the Educational Background of Melvin L. Silberman and How is the Method of Listening Team Melvin L. Silberman's Perspective in Islamic Education." While the research objective is to provide a clear picture of Melvin L. Silberman's educational background and to explain the listening team method according to Melvin L. Silberman in Islamic Religious Education. This research uses a library research approach and the type of research carried out is descriptive qualitative. There are two data sources used, the primary source, namely the book Active Learning by Melvin L. Silberman, and the secondary source, namely journals, theses and books that discuss the listening team method. In data collection, researchers used document studies, and then in data analysis using content analysis (Contant analysis). The results of this study are twofold, namely: 1. Melvin L. Silberman is a lecturer at Temple University, from his work in the field of education, for 25 years he has had the pleasant experience of working with pre-service and service teachers at all levels of education. He is able to create Active Learning methods to make learning active. He created several methods that were assisted by his friends and students at Temple University, one of which was the listening team. 2. According to Melvin L. Silberman listening team or listening team is an activity which is a way to help students stay focused and observant during lecture-based teaching. Listeners are small groups that are responsible for clarifying the subject matter. The listening team method is a cooperative learning model that requires students to think critically, each group has a different task, there is a questioning team, an approving team, a rebuttal team and a sampling team